Models, Simulation, and Experimental Issues in Structural Mechanics - Frémond, Michel; Maceri, Franco; Vairo, Giuseppe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The reader aware in Structural Mechanics will find in this book a source of fruitful knowledge and effective tools useful for imagining, creating, and promoting novel and challenging developments. It addresses a wide range of topics, such as mechanics and geotechnics, vibration and damping, damage and friction, experimental methods, and advanced structural materials. It also discusses analytical, experimental and numerical findings, focusing on theoretical and practical issues, and leading to innovations in the field. Collecting some of the latest results from the Lagrange Laboratory, a European scientific research group, mainly consisting of Italian and French engineers, mechanicians and mathematicians, the book presents the most recent example of the long-term scientific cooperation between well-established French and Italian Mechanics, Mathematics and Engineering Schools. .
Keywords: Mechanics, Applied; Solids; Mathematics -- Data processing; Materials; Multibody systems; Vibration; Engineering design; Solid Mechanics; Computational Science and Engineering; Materials Engineering; Multibody Systems and Mechanical Vibrations; Engineering Design